Resource use associated with type 2 diabetes in Africa, the Middle East, South Asia, Eurasia and Turkey: results from the International Diabetes Management Practice Study (IDMPS) - Gagliardino, Juan José (2017)
Objective: Type 2 diabetes (T2D) and its complications form a global healthcare burden but the exact impact in some geographical regions is still not well documented. We describe the healthcare resource usage (HRU) associated with T2D in Africa, the Middle East, South Asia, Eurasia and Turkey. Research design and methods: In the fifth wave of the International Diabetes Management Practices Study (IDMPS; 2011-2012), we collected self-reported and physician-reported cross-sectional data from 8156 patients from 18 countries across 5 regions, including different types of HRU in the previous 3-6 months. Negative binomial regression was used to identify parameters associated with HRU, using incidence rate ratios (IRRs) to express associations. Results: Patients in Africa (n=2220), the Middle East (n=2065), Eurasia (n=1843), South Asia (n=1195) and Turkey (n=842) experienced an annual hospitalization rate (mean±SD) of 0.6±1.9, 0.3±1.2, 1.7±4.1, 0.4±1.5 and 1.3±2.7, respectively. The annual number of diabetes-related inpatient days (mean±SD) was 4.7 ±22.7, 1.1±6.1, 16.0±30.0, 1.5±6.8 and 10.8±34.3, respectively. Despite some inter-regional heterogeneity, macrovascular complications (IRRs varying between 1.4 and 8.9), microvascular complications (IRRs varying between 3.4 and 4.3) and, to a large extent, inadequate glycemic control (IRRs varying between 1.89 and 10.1), were independent parameters associated with hospitalization in these respective regions. Conclusions: In non-Western countries, macrovascular/microvascular complications and inadequate glycemic control were common and important parameters associated with increased HRU.